Penerapan Rom Exercise Bola Karet Untuk Meningkatkan Kekuatan Otot Genggam Pasien Stroke Di RSUD Dr. Moewardi Surakarta - Ambika Anggardani; Ida Nur Imamah; Isti Haniyatun (Pusat riset dan Inovasi Nasional, 2023)
Background; Stroke is a blood circulation disorder in the brain which results in the death of brain tissue. Stroke patients who experience hemiparesis can result in functional impairment, impaired mobility, impaired daily activities and irreversible disability. Purpose: This study aims to determine the results of implementing rubber ball ROM exercise on muscle strength in non-hemorrhagic stroke patients. Methods: The application was carried out using a descriptive method with a case study design in non-hemorrhagic stroke patients who are at risk of experiencing muscle weakness. The application of the rubber ball rom exercise was carried out for 4 consecutive days by holding the rubber ball for 5 seconds and repeated 7 times. Results: There was an increase in muscle strength of 1 degree in both respondents after the rubber ball ROM exercise. Conclusion: The results of the application to the two respondents between before and after being given the rubber ball ROM exercise showed an increase in muscle strength. So that rubber ball ROM exercise can be used as a non-pharmacological technique to increase muscle strength in stroke patients.